Estudo da morfologia e análise molecular dos parasitos de Geophagus proximus castelnau, 1855 (Cichlidae, perciformes) provenientes do reservatório de Ibitinga, médio Rio Tietê, São Paulo, Brasil - Rocha, Rodrigo Severiano (2018)
Descriptive taxonomy studies of Tetê river fish helminths are relevant, given the great heterogeneity of the hosts described for the site. Geophagus proximus perciforme fish freshwater in South America, is a little studied species, given their importance in the food chain candy environments and their business relevance. The Ibitinga Reservoir is located in the basin of the river Tiete - Parana, and due to dam its waters resulted largely from its flooded banks, making this part of the river, in the municipality of Ibitinga, extremely deep and a great victim of eutrophication. This study analyzed the parasitism of Geophagus proximus (Castelnau, 1855) using as tools light microscopy and molecular biology for the taxonomic study of the helminths found. The results of the molecular analyzes (amplification and sequencing of the Cytochrome c oxidase I gene) revealed the occurrence of Austrodiplostomum ostrowskiae in the eyes of the analyzed individuals and the morphology of the parasite specimens of the brain showed the occurrence of Austrodiplostomum compactum. The research results also indicated that the most parasitized organs were the gills, in which ectoparasites belonging to the Monogenea class were found. Thus, the analysis of the fauna of parasites of G. proximus represents a great ally in studies of parasitic taxonomy. Based on this context, the present study contributes with important data for the global biodiversity of the parasites, with great possibilities to describe new species.